Perencanaan Sistem Kelistrikan Pada Alat Penjernih Air Tipe Portable Berbasis Panel Surya - Aswad Gifari; Ahmadil Amin; Heri Irawan (Politeknik Negeri Semarang, 2026)
The clean water crisis in remote and post-disaster areas remains a pressing issue, particularly due to the limited supply of conventional electrical energy. This situation demands the development of innovative solutions in the form of simple, efficient, and sustainable portable technology. This study aims to design and test a solar panel-based water purification system without an inverter, which can operate independently by utilizing abundant renewable energy sources in Indonesia. The research method was implemented through prototype design, system assembly, and direct testing using a quantitative experimental approach. The parameters observed included solar radiation intensity, voltage, current, solar panel input-output power, panel efficiency, pump input-output power, water flow, and pump efficiency. The measurement data were analyzed descriptively to assess the overall system performance. The results showed a significant correlation between radiation intensity and system performance. The highest radiation intensity value was 152.66 W/m² at 1:00 PM, with a panel input power of 149.67 W and an output power of 53.78 W. The highest panel efficiency reached 35.93%, while the pump efficiency ranged from 20.1 to 28.1%, with a maximum discharge of 0.000308 m³/s.